Artificial Intelligence in the Perspectives of Agricultural Technology Development in Indonesia - Dwi Santoso; Deny Murdianto (Budapest International Research and Critics University, 2022)
The agricultural sector is a sector supporting economy and welfare of many people in Indonesia. The direction of life development of Indonesian people themselves has been headed todominant direction, preferring practical and dynamic activity. This of course indirectly influences the point of view of the farmers to do their farming activities using more practical and modern things. Traditional ways have gradually been abandoned, although there are still some farmers we still use them. The development of modern technology in all fields, particularly in agriculture, is certainly very helpful for farmers in terms of saving time and energy. Artificial intelligence systems adopting human mindset into a computer programming language can create technology that works like a human, with training data that has been examined into programming languages.